Comparative experimental evaluation and thermodynamic analysis of the possibility of using degraded C15-C50 crankcase oil waste as thermal storage materials in solar drying systems. (1st July 2022) - Ndukwu, M.C.; Edet Ben, Augustine; Lamrani, B.; Wu, Hongwei; Bennamoun, L.; Abam, F.I.
Highlights: Solar dryer with liquid thermal storage infused in copper tubes to form a composite heat exchanger is investigate. Used C15 -C50 crankcase oil formed part of the liquid thermal storage materials investigated. Paraffin and C15 – C50 crankcase oil exhibited a maximum thermal storage temperature difference of about 10.8 °C above ambient temperature. The average exergy efficiency of 45–49.9% were achieved for using thermal storage material. Used C15 -C50 crankcase oil showed a prospect as a suitable heat storage medium in solar drying design. Abstract: The study presents a comparative thermodynamic analysis of degraded C15 -C50 grade crankcase oil (DCO) and paraffin thermal storage (PTS) as heat storage materials in solar drying. The goal is to convert DCO from waste to a useful product in solar drying. The assessment was based on drying efficiency, energy and exergy analysis, sustainability assessment and CO2 mitigation of each solar dryer. The difference in drying efficiency between the dryer with DCO and that with PTS is less than 1.5 % while the difference between the specific energy consumption is less than 9 %. In contrast, the difference between the dryer with DCO and that without thermal storage is 24.2 %. The mean exergy efficiency ranged between 41.6 and 49.9 %. The values of the waste exergy ratio (WER), sustainability index (SI) and improvement potential (IP) for the three dryers ranged from 0.00 ≤ WER ≤ 1.00, 0.00 ≤ SI ≤ 34.56, 0.00 ≤ IP ≤ 2.68 kW. Using these dryers instead of diesel, grid-based electricity or coal-powered dryer will limit a maximum of 5, 792, 826 tons of CO2 from the atmosphere.